EFFECTS OF KINESIOTAPING ALONG WITH QUADRICEPS STRENGTHENING EXERCISES ON PAIN, JOINT RANGE OF MOTION AND FUNCTIONAL ACTIVITIES OF KNEE IN SUBJECTS WITH PATELLOFEMORAL OSTEOARTHRITIS (International Journal of Physiotherapy, 2014)
Background: Patello femoral Osteoarthritis is the most common degenerative disease in older age group, causing pain, physical disability, and decreased quality of life.As many treatment options available, kinesiotaping is an efficacious treatment for management of pain & disability in patellofemoral joint osteoarthritis. Previous studies have shown that kinesiotaping as well as quadriceps strengthening significantly yields functional benefits. But there is lack of evidence revealing combined effectiveness & effects of kinesiotaping along with quadriceps strengthening in subjects with patellofemoral joint osteoarthritis.Methods: 30 subjects with symptoms of patellofemoral osteoarthritis fulfilled the inclusion criteria were randomly assigned into 2 groups of 15 in each group. Taping along with quadriceps strengthening program is compared to the quadriceps strengthening program alone. Pain were measured by Visual Analogue Scale (VAS), knee ROM were measured by Goniometer, Functional status were measured by Western Ontario McMaster Universities index (WOMAC), score. Measurements were taken pre & post intervention.Results: The results indicated that kinesiotaping along with quadriceps strengthening exercises showed there was statistically significant improvement in pain (